A narrative overview of utilizing biomaterials to recapitulate the salient regenerative features of dental-derived mesenchymal stem cells - Sevda Pouraghaei Sevari; Sahar Ansari; Alireza Moshaverinia (Nature Publishing Group, 2021)
Abstract Tissue engineering approaches have emerged recently to circumvent many limitations associated with current clinical practices. This elegant approach utilizes a natural/synthetic biomaterial with optimized physiomechanical properties to serve as a vehicle for delivery of exogenous stem cells and bioactive factors or induce local recruitment of endogenous cells for in situ tissue regeneration. Inspired by the natural microenvironment, biomaterials could act as a biomimetic three-dimensional (3D) structure to help the cells establish their natural interactions. Such a strategy should not only employ a biocompatible biomaterial to induce new tissue formation but also benefit from an easily accessible and abundant source of stem cells with potent tissue regenerative potential. The human teeth and oral cavity harbor various populations of mesenchymal stem cells (MSCs) with self-renewing and multilineage differentiation capabilities. In the current review article, we seek to highlight recent progress and future opportunities in dental MSC-mediated therapeutic strategies for tissue regeneration using two possible approaches, cell transplantation and cell homing. Altogether, this paper develops a general picture of current innovative strategies to employ dental-derived MSCs combined with biomaterials and bioactive factors for regenerating the lost or defective tissues and offers information regarding the available scientific data and possible applications.